Performance Analysis of Hadoop MapReduce And Apache Spark for Big Data - Adesokan, Adeyemi (My University, 2020)
In the recent era, information has evolved at an exponential rate. In order to obtain new insights, this information must be carefully interpreted and analyzed. There is, therefore, a need for a system that can process data efficiently all the time. Distributed cloud computing data processing platforms are important tools for data analytics on a large scale. In this area, Apache Hadoop (High-Availability Distributed Object-Oriented Platform) MapReduce has evolved as the standard. The MapReduce job reads, processes its input data and then returns it to Hadoop Distributed Files Systems (HDFS). Although there is limitation to its programming interface, this has led to the development of modern data flow-oriented frameworks known as Apache Spark, which uses Resilient Distributed Datasets (RDDs) to execute data structures in memory. Since RDDs can be stored in the memory, algorithms can iterate very efficiently over its data many times. Cluster computing is a major investment for any organization that chooses to perform Big Data Analysis. The MapReduce and Spark were indeed two famous open-source cluster-computing frameworks for big data analysis. Cluster computing hides the task complexity and low latency with simple user-friendly programming. It improves performance throughput, and backup uptime should the main system fail. Its features include flexibility, task scheduling, higher availability, and faster processing speed. Big Data analytics has become more computer-intensive as data management becomes a big issue for scientific computation. High-Performance Computing is undoubtedly of great importance for big data processing. The main application of this research work is towards the realization of High-Performance Computing (HPC) for Big Data Analysis. This thesis work investigates the processing capability and efficiency of Hadoop MapReduce and Apache Spark using Cloudera Manager (CM). The Cloudera Manager provides end-to-end cluster management for Cloudera Distribution for Apache Hadoop (CDH). The implementation was carried out with Amazon Web Services (AWS). Amazon Web Service is used to configure window Virtual Machine (VM). Four Linux In-stances of free tier eligible t2.micro were launched using Amazon Elastic Compute Cloud (EC2). The Linux Instances were configured into four cluster nodes using Secure Socket Shell (SSH). A Big Data application is generated and injected while both MapReduce and Spark job are run with different queries such as scan, aggregation, two way and three-way join. The time taken for each task to be completed are recorded, observed, and thoroughly analyzed. It was observed that Spark executes job faster than MapReduce.
Keywords: big data; data processing; cloud services; distributed systems; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; Master’s Programme in Wireless Industrial Automation